Study on site of acute myocardial infarction associated with arrhythmias and outcome - Patil, Basavaraj M. (International Journal of Advances in Medicine, 2017)
Background: Despite considerable progress, Arrhythmias remain a major cause of death in patients with myocardial infarction. Majority of these arrhythmias occurring within the first 24 hours. Few studies have shown that, frequently associated different arrhythmias with various distributions of myocardial infarctions. The aim of the present study is to identify the type of arrhythmias and outcome in patients presenting with acute myocardial infarction. Methods: A total of 100 patients admitted to the ICC unit of govt. general hospital, Gulburga & Basaveshwar teaching & general hospital Gulburga from one year data were taken for present study. The risk factors for cardiac disease were evaluated through history, physical examination and blood investigations. All the patients were monitored for 48-72 hours for arrhythmias. Type and time of onset arrhythmias was also noted. Results: Out of the 100 patients with myocardial infarction studied, 76 patients had arrhythmias. Majority of arrhythmias occurred during less than 12 hours and sinus tachycardia was the commonest arrhythmia (40%). The overall incidence of mortality was 15%. Majority of mortality occurs with 24 hours (66.6%). Mortality was more in males (16.25%) than female (10%). Cardiogenic shock (40%) and left ventricular failure (33.33%) were the most common cause of death. Conclusions: Arrhythmia occurred in 76% of the patients with acute myocardial infarction. Sinus tachycardia was the most common arrhythmia constituting about 40% of patients who had arrhythmias.